An exploration of the meaning of social justice for survivors of domestic violence in Zimbabwe - Zvobgo, Ellen Farisayi (African Studies, 2023)
Globally, the WHO (2014: 10) estimates that one in three women experiences sexual and physical violence at the hands of their intimate partner over their lifetime. According to a Violence Against Women (VAW) Baseline study (2013: 11) in Zimbabwe- two in every three (68%) women who were interviewed reported having experienced some type of gendered violence during their lifetime. Although legislation on the prevention of domestic violence has become, globally, part of many countries' legal frameworks, Zimbabwe instantiated its Domestic Violence Act only in 2007. This came as a result of decades of feminist advocacy at state, legal, and NGO levels which theorized the rights of survivors of domestic violence, usually women as essential to Zimbabwean citizenship. These rights included criminalization of domestic violence and full access to legal processes. As in many other contexts, the weak implementation of this legislation has been widely researched, suggesting that Zimbabwean domestic abuse survivors remain vulnerable (Burton, 2008). Alongside the need for more research lies the question at the heart of this dissertation. Feminist theory has established that the vulnerability of domestic abuse survivors comprises both the legal and the social. Theorists of social justice focus on questions of recognition and redistribution (Fraser, 2008), empowerment (Kabeer, 2016) and the notion of capabilities as intrinsic to fair and equitable social systems and processes (Nussbaum, 2011). This study asks whether and how the provision of shelter space to the survivors (for which provision is made in the Domestic Violence Act) can be theorized as a form of social justice, despite the weakness of the system of courts. In carrying out the study, I worked with one particular shelter, Musasa, in Gweru, Zimbabwe, and explored the experiences of those who had worked with the shelter in multiple ways. This built what I called an “exploded view” of the representations of living and working at a specific place. The concept of “exploded view” comes from architecture and connotes a perspective able to understand different parts of a system or process separately to revise the whole. Data gathering was through in-depth interviews and involved listening to the voices of those who imagined and created the shelter and also those running it. At the centre of the study were twenty women who experienced the shelter as a space in which they lived and their voices were critical in theorising sheltering. Data were analysed using both thematic and content analysis and aimed to tease out the multiple threads of meaning through which people associated with the shelter in different ways made sense of its location and importance for tackling domestic violence in Zimbabwe. While the study is aware of its limitations as a case study, the dissertation's theorization of shelter work as social justice contributes to a feminist theorization of redress for survivors of domestic abuse in Zimbabwe.